DURAÇÃO DA QUALIDADE DE OVOS ESTOCADOS DE POEDEIRAS COMERCIAIS DE DIFERENTES IDADES - MENDONÇA, Ana Paula Vargas,; MARCELO, Gislaine de Castro,; LONGO, Luise Fernanda da Rocha,; SANTANA, Patrícia Gomes,; BAIRROS, Eliane Corrêa,; GARCIA, Elis Regina de Moraes, (ANAIS DO ENIC, 2023)
-